2008
DOI: 10.1111/j.1440-1827.2008.02257.x
|View full text |Cite
|
Sign up to set email alerts
|

Ocular adnexal IgG4‐related disease has uniform clinicopathology

Abstract: IgG4-related disease is a recently proposed clinical entity with several unique clinicopathological features. Ocular adnexal IgG4-related disease, however, has not well been clarified. The purpose of the present study was to examine 21 patients (10 men, 11 women; age range, 39-86 years) with ocular adnexal IgG4-related disease. In 17 out of 21 patients (81%), the lacrimal glands were involved and bilateral lacrimal gland swelling was frequently observed (n = 12; 70.6%). In contrast, the conjunctiva was not inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
267
1
9

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 270 publications
(291 citation statements)
references
References 23 publications
13
267
1
9
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9][10] Clinical manifestations are apparent in the pancreas, bile duct, gallbladder, lacrimal gland, salivary gland, retroperitoneum, kidney, lung, and prostate, in which tissue fibrosis is pathologically induced. [1][2][3][4][5][6][7][8][9][10] Recently, many cases have been reported in Western countries, as well as in Japan. 3 However, the precise pathogenesis and pathophysiology of IgG4-related disease remain unclear.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[1][2][3][4][5][6][7][8][9][10] Clinical manifestations are apparent in the pancreas, bile duct, gallbladder, lacrimal gland, salivary gland, retroperitoneum, kidney, lung, and prostate, in which tissue fibrosis is pathologically induced. [1][2][3][4][5][6][7][8][9][10] Recently, many cases have been reported in Western countries, as well as in Japan. 3 However, the precise pathogenesis and pathophysiology of IgG4-related disease remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…As patients presenting with prominent fibrosis are frequently suspected of having malignant tumors, IgG4-related disease should be considered in the differential diagnosis to avoid unnecessary surgery. [1][2][3][4][5][6][7][8][9][10] Recent studies have reported that IgG4-related disease sometimes involves the systemic lymph nodes but clinicopathological characteristics have not been well documented yet. 3,4,11 In this study, we sought to clarify the clinicopathologic features of systemic IgG4-related lymphadenopathy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some case reports have showed effectiveness of methotrexate (105), cyclosporine (106), and cyclophosphamide (106,107).…”
Section: Steroid-sparing Immunomodulatorsmentioning
confidence: 99%